Contributions to the International Anti-Corruption Summer Academy 2011 (Practice Meets Science - Contemporary Anti-Corruption Dialogue, 2012)
The present volume is a collection of articles written by renowned anti-corruption academics and practitioners who lectured at IACSA, a summer programme organized by the International Anti-Corruption Academy from 30 June to 9 July 2011.--